The initial stage of criminal proceedings under the legislation of the Russian Federation - Makeeva, Inna Vladimirovna; Zeynalova, Larisa Mikhailovna; Prudnikov, Mikhail Nikolaevich; Aminov, Ilya (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the characterization of the procedure for initiation of criminal cases under the legislation of the Russian Federation. The sources of information about crimes that trigger appropriate response measures are investigated. A detailed coverage of the order of receipt of information about the crime, as well as the reflection of this information in the documentation of the law enforcement agency. Particular attention is paid to ensuring the rights and legitimate interests of victims of crimes, as well as those in respect of whom the issue of initiation of criminal case is being resolved.